Textuality standards of goods labels and packaging - Kovalchuk, Iryna; Popivniak, Olena (Current issues of Ukrainian linguistics: theory and practice, 2021)
This article deals with the food and drink names. Special attention is given to the peculiarities of goods names in the context of textuality. Names of the beverages and eatables verbalize all features, qualities and individual characteristics of these goods. They create the naming space that consists of four nominative components: brand, individual, genitive, and functional descriptive. These nominative components create the text of labels and packages. Four nominative components function as corresponding text information blocks. It means that food and drink names labels combine two spaces. The first space is naming that is represented with the integrated naming complex. The complex grasps four nominative components. The second space is informational that stores the necessary volume of information and creates a communicative background. The information scope is kept in the text construction. The whole volume is divided into four relevant text blocks. Together all these blocks form text boundaries which outline the text construction. This text construction is characterized with two interdependent features coexisting in the integrated naming complex such as cohesion and coherence. Cohesion is realized on the lexical level involving the mechanism of repetition which is the part of the interaction. On the other hand, the repetition may be complete (the naming unit is repeated literally) and partial (the naming unit is repeated partly). The repetition may be between nearest blocks (having common boundary) and distant blocks (without common boundary). There is some peculiarity in the structure of functional-descriptive text block which functions as a set of subblocks. These subblocks are grasped into four subblock clusters. It indicates that description of goods properties and their usage instructions are significant in the text construction of labels and packages. The results of the research broaden the set of naming units adding to word, phrase, and sentence the next unit recognized as a text.
Keywords: beverage, foodstuffs, label, packaging, text block, text subblock.